Emotional Tone and Authenticity of World Governments’ Discourse Concerning Monkeypox: A Psycholinguistics Analysis - Bahtiar, Jessica Yunanda; Indah, Rohmani Nur (Universitas Sanata Dharma, 2024)
The discourses of Monkeypox relating to linguistics segments may contain a person's emotional tone and authenticity discourse from psychology. This article presents a psycholinguistic analysis of the discourse used by world governments during the monkeypox outbreak. It examines the emotional tone and authenticity of the language used by government officials in their discourses to the public. Therefore, this study used psycholinguistics analysis which adopt the Linguistics Inquiry Word Counts (LIWC) program to compute the text into a word count numbers with the average number of emotional tone and authenticity. The findings showed that emotional tone and authenticity of the discourse can have a significant impact on how the audience receives and interprets the message. Accordingly, the use of authentic communication strategies can enhance public trust and confidence in the government's ability to manage a crisis. It brings the implication that government officials should use language features that reflect a high level of authenticity, such as first-person pronouns and negative adjectives, to establish trust and confidence in their leadership during a public health crisis.